2022
DOI: 10.1021/acs.cgd.2c00654
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Two Crystalline Forms on the Multiple Melting and Crystallization Kinetics of Thermoplastic Polyurethane

Abstract: Exploring the origin of multiple melting of thermoplastic polyurethane (TPU) is of great significance for comprehending the mechanism for its phase transition. Herein, the effects of two crystal forms (Form-I and Form-II) and crystal form transition on the melting behaviors and crystallization kinetics of TPU are reported. As the function of the crystallization temperature (T c ), Form-II and Form-I develop at T c ≥ 130 °C and T c ≤ 130 °C, respectively, which leads to distinct differential scanning calorimetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…A lower-temperature endotherm is consistently observed roughly 35 C above T a , in agreement with the expected range of roughly 20-40 C. 78 This peak is nearly independent of composition except at very low and very high T a . This has been assigned to the melting of the initially formed ordered structure, 50,79 in this case the increasing fraction of ordered paracrystalline domains due to the annealing procedure, or to relaxation of interfacial structures. 80 The monotonic behavior with T a had earlier been attributed to ordering of progressively longer hard segment sequences with increasing T a .…”
Section: Thermal Responsementioning
confidence: 99%
“…A lower-temperature endotherm is consistently observed roughly 35 C above T a , in agreement with the expected range of roughly 20-40 C. 78 This peak is nearly independent of composition except at very low and very high T a . This has been assigned to the melting of the initially formed ordered structure, 50,79 in this case the increasing fraction of ordered paracrystalline domains due to the annealing procedure, or to relaxation of interfacial structures. 80 The monotonic behavior with T a had earlier been attributed to ordering of progressively longer hard segment sequences with increasing T a .…”
Section: Thermal Responsementioning
confidence: 99%
“…So far, researchers mainly focused on single component TPU systems, and the study on TPU blends was still rare. 35,36 Xu et al investigated the effect of water absorption on the T g and the degree of phase separation of thermoplastic polyurethane blends by dynamic mechanical analysis, FTIR spectroscopy, and SAXS. 37 It was concluded that hydrogen-bound water rather than free water weakened the interfacial state between the soft and hard domains, thus lowering the T g of the samples.…”
mentioning
confidence: 99%